Fælleseuropæisk sikkerhed. Transnationale Socialdemokratiske netværk, afspændingspolitikkens krise og Ostpolitikkens videreførelse - Mariager, Rasmus (Historisk Tidsskrift, 2013)
All-European Security Transnational Social Democratic Networks, the Crisis of Détente, and the Continuation of OstpolitikIn the late 1970s and early 1980s, relationships became strained between the United States and a number of West European countries. The present article investigates the specific role of the West European Social Democratic parties in this context, with particular focus on the role of values and ideas in shaping perceptions and priorities of political players. European Social Democrats had been firm and loyal supporters of the Atlantic partnership since the formation of the Atlantic Pact in 1949. During the early Cold War, the fundamental conflict between Communist and Capitalist systems determined, in large measure, their policies. Even later, they remained faithful to the same fundamental positions. Nevertheless, during the 1970s the arms race, including innovations in the technology and tactics of nuclear warfare, modified the attitude of the Labour parties. They and many other Europeans feared that in case of war the battlefield would be in Western and Central Europe, not the Soviet Union or the United States. The Labour parties increasingly tried to make their influence felt in matters of the East-West Divide. Social Democratic party delegations travelled to Moscow and expressed, visiting the Kremlin, their desire to end the confrontation. At the same time, they emphasized that Social Democrats did not shrink from competition between Communism and democratic Socialism, be it in terms of ideology or economic performance. Disagreement over the political strategy of NATO towards its East Bloc counterpart was growing between the United States and parts of Western Europe. Many leading North European politicians had since the early 1950s been in general support of détente policies, whereas the United States had been more hesitant. Following the Helsinki accords in August 1975, this divide within NATO was aggravated to a degree that justifies talking about two competing Grand Strategies. The United States, supported by European Conservatives, wanted to conduct a policy of strength, whereas Social Democratic politicians, especially from North Western Europe, preferred to continue the so-called Ostpolitik – a brand of German origin – that had been so vital for the détente process. Following 1975, joint efforts to that effect were weaker; but the process did not stop entirely, at least not in Europe. Washington may have abandoned it temporarily, but a large number of leading European Social Democratic politicians strived to keep the idea alive. They continued to promote the same Ostpolitik that had been conducive to the Conference on Security and Cooperation in Europe. In the late 1970s and early 1980s, this coordinated, transnational Social Democratic activity – mainly inspired by Willy Brandt and Egon Bahr, but supported by other prominent Social Democratic leaders – may have appeared less powerful than one would expect of a Grand Strategy. In fact, on national levels it had the air of improvisations, as Labour parties constantly struggled with Liberal and Conservative parties over these issues. Indeed, domestic politics – the appeal by Social Democrats to widespread anti-war values and sentiments among voters – may be the most important single factor in order to explain why their security policies, albeit in different ways, were sharpened according to the general pattern described in this article.